Social skills and their relationship to personal well-being among kindergarten students (Journal of the College of Basic Education, 2022)
The current research aims to identify1- Social skills of female students in the kindergarten department.2-The personal well- being of female students in the kindergarten department3- The correlational relationship between personal well-being and social skills of female students in the kindergarten department.The current research was determined by the female students of the Kindergarten Department at the College of Education for Girls / University of Baghdad, for the academic year (2018-2019). The research sample consisted of (100) students chosen in a random class method and with equal distribution. To achieve the objectives of the research, the two researchers built the scale of social skills, which is composed of (29) paragraphs and the Personal well-being Scale, consisted of (22) paragraphs. The two scales were presented to a group of experts in the field of educational and psychological sciences and the field of kindergartens. The reliability indicators were used, namely the apparent reliability and constructive reliability , and reliability extracted for each scale by the Alpha Cronbach equation. After applying the scales to the sample members, the data were analyzed and processed statistically with the Statistical Program for Social Sciences (SPSS), and the research reached the following results:The students of the kindergarten department enjoy with social skills and personal well-being .There is correlation, which is a non-statistically significant relationship between social skills and personal well-being among students of the kindergarten department.In light of the results, the two researchers put forward a number of recommendations and proposals